PENEGAKAN HUKUM TERHADAP PELAKU TINDAK PIDANA MELAKUKAN EKSPLOITASI SECARA EKONOMI DAN SEKSUAL TERHADAP ANAK DI WILAYAH HUKUM KEPOLISIAN RESOR KOTA PEKANBARU - Trie Sundari; Emilda Firdaus; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
In Indonesia, crimes that often occur are trafficking in persons against minors who are exploited economically or sexually. The majority of victims of exploitation crimes are women and children. The main factors causing women and children to become victims of this crime are low levels of education and limited knowledge about their rights so that they are often used by perpetrators to fool victims with the aim of finding work. Based on cases of child trafficking that occurred in Indonesia according to the Indonesian Child Protection Commission (KPAI) that the police must act decisively related to trafficking in persons and exploitation of children, because child traffickers are increasingly rampant in Indonesia so it requires firm measures by law enforcement officials.Under the child protection law that every person is prohibited from placing, allowing, committing, committing to do, or participating in economic and / or sexual exploitation of children. The purpose of writing this thesis, namely: First to find out how law enforcement against perpetrators of criminal acts to exploit economically and sexually against children in the jurisdiction of Pekanbaru City Police, Second to find out the obstacles in law enforcement against perpetrators of criminal acts to exploit economically and sexually against children in the jurisdiction of the Pekanbaru City Police Department.Keywords: Law Enforcement - Criminal Acts - Perpetrators - Economic and Sexual Exploitation - Children